Prevalence of dental caries in the Late Neolithic and Early Bronze Age populations from Żerniki Górne (Poland) - Tomczyk, Jacek; Rusin, Paweł; Zalewska, Marta (Anthropological Review, 2021)
The aim of the studies is to describe the prevalence and distribution of dental caries in two populations from Żerniki Górne (Poland). The first population represented the Corded Ware Culture (CWC) (2550–2350 BC), and the second population belonged to the Trzciniec Culture (TC) (1300–1000 BC). While the TC is identified with a typically agricultural strategy, the CWC culture strategy is still debatable. Two types of strategies are indicated in the CWC, either a mixed or typical agricultural economy. A total of 110 adults were examined, of which 29 represented the CWC and 81 belonged to the TC. A total of 1132 permanent teeth were examined (CWC 379, TC 753). Of the 110 individuals, 54 individuals had dental caries (CWC 19/29, 66%; TC 35/81, 43%). In the CWC, 68% (13/19) of males and 60% (6/10) of females had dental caries. In the younger period (TC), the percentage of dental caries among males was little higher (45%) than among females (41%). Dental caries was identified in 13% (50/379) of the teeth from the CWC. In the TC, the percentage of affected teeth were similar (11%, 82/753). The most common location of caries in all the chronological periods were the approximal and cemento-enamel junction [CEJ] surfaces. Caries on the occlusal surface was much less frequent. If we assume that an important cause of the development of dental caries is a high-carbohydrate diet, we can conclude that a similar prevalence of teeth affected by caries and it locations indicate a similar management strategy in both populations.